Metode Profile Matching Dalam Mendukung Keputusan Perpanjangan Asisten Dosen - Martini; Nani Agustina; Entin Sutinah (Journal of Students‘ Research in Computer Science, 2022)
Lecturer assistants are apprentice students whose job is to assist lecturers in teaching and learning activities in class. There are 10 students who are doing internships as teaching assistants. At the end of each semester the Training Division in a university conducts an evaluation of the assessment of students who are apprentices as teaching assistants. However, currently the training department has not yet found the right method for making decisions to determine teaching assistants who deserve to be extended for internships in the following semester. Currently, decision making is based on an assessment of the ability to explain the material when the lecturer concerned is unable to attend, although there are still many assessment criteria that can be considered in decision making. To solve this problem, this study adopts a method in making decisions on the extension of teaching assistants by using the Profile Matching method which includes several assessment criteria including attendance, neatness of dress, loyalty, work performance, responsibility, obedience, honesty, cooperation, initiative and leadership. From this criterion, it will be included in the Core Factor and Secondary Factor with the criteria of very good, good, pretty good, not good and very bad scores, so that in this research a decision was made to extend teaching assistants in the following semester, namely by choosing 4 teaching assistants who each has the following assessment results: AST9 with a value of 4.9, AST10 with a value of 4.8, AST1 with a value of 4.4 and AST8 with a value of 4.4. Keywords: Assistant Performance, Decision, Matching Profile   Abstrak  Asisten dosen merupakan mahasiswa magang yang tugasnya membantu dosen dalam kegiatan belajar mengajar di kelas. Terdapat 10 orang mahasiswa yang sedang magang menjadi asisten dosen. Pada setiap akhir semester bagian pelatihan yang terdapat dalam suatu Universitas mengadakan evaluasi penilaian terhadap mahasiswa yang magang sebagai asisten dosen. Namun saat ini bagian pelatihan masih belum menemukan metode yang tepat dalam melakukan pengambilan keputusan untuk menentukan asisten dosen yang layak diperpanjang untuk magang di semester berikutnya. Saat ini pengambilan keputusan berdasarkan penilaian dari kemampuan menjelaskan materi pada saat dosen yang bersangkutan berhalangan hadir, walaupun masih banyak kriteria penilaian yang dapat menjadi pertimbangan dalam pengambilan keputusan. Untuk memecahkan masalah tersebut, penelitian ini mengambil metode dalam pengambilan keputusan perpanjangan asisten dosen dengan menggunakan metode Profile Matching yang meliputi beberapa kriteria penilaian diantaranya Absensi, Kerapihan berpakaian, Kesetiaan, Prestasi Kerja, Tanggung Jawab, Ketaatan, Kejujuran, Kerjasama, bPrakarsa dan Kepemimpinan. Dari kriteria ini akan dimasukkan ke dalam Core Factor dan Secondary Factor dengan keriteria nilai sangat baik, baik, cukup baik, kurang baik dan sangat kurang baik, sehingga dalam penelitam ini dihasilkan sebuah keputusan perpanjangan asisten dosen di semester berikutnya yaitu dengan memilih empat asisten dosen yang masing-masing memiliki hasil penilaian sebagai berikut: AST9 dengan nilai 4,9, AST10 dengan nilai 4,8, AST1 dengan nilai 4,4 dan AST8 dengan nilai 4,4. Kata Kunci: Keputusan, Kinerja Asisten, Profile Matching